RISK FACTORS OF BLADDER CANCER PATIENTS IN ARIFIN ACHMAD REGIONAL GENERAL HOSPITAL, RIAU PROVINCE, INDONESIA - Zamzami, Zuhirman (Indonesian Journal of Urology, 2022)
Objective: This study aims to describe the risk factors of bladder cancer patients in Arifin Achmad Regional General Hospital, Riau Province, Indonesia. Material & Methods: We reviewed the medical records of bladder cancer patients managed in Arifin Achmad Regional General Hospital from January 2013 - December 2017. The data collected were sex, age, histopathology types, staging, smoking history, occupation, ethnic/tribes, and city/district origine. Statistical analysis of univariate was used. Approval on the study was obtained from the Ethical Review Board for Medicine and Health Research, Medical Faculty, University of Riau. Results: There were 101 bladder cancer patients consisting of 83.2% patients with transitional cell carcinoma and 65.3% with advanced stage. The result showed the most common (82.2%) patients were males and 35.6% of patients were in age 51-60 year old group, with the youngest was in 9 year old group and the oldest is 85 years. The most common risk factors of bladder cancer patient were farmers in 29.7% and the non-smoking patients were in 52.5%, Malay ethnic in 30.7% and Pekanbaru origin in 30.7% of patients. Conclusion: Bladder cancer risk factors in Arifin Achmad Regional General Hospital were males, farmers, Malay ethnic, and Pekanbaru origin.